Green infrastructure : linking landscapes and communities - Benedict, Mark A.; McMahon, Edward, 1947-; Conservation Fund (Arlington, Va.) (Washington, DC : Island Press, 2006)
"Those engaged in land conservation and management increasingly have come to envision a process that connects environmental, social, and economic health: Green Infrastructure. For the landscape designer, conservation-minded planner, and the concerned citizen, this work presents principles and practices to create conceptual and real links in communities across the country." "With illustrative and detailed examples, Green Infrastructure advances smart conservation: large-scale thinking and integrated action to plan, protect, and manage our natural restored lands. Providing both the historical framework for the importance of greenways and green space networks and practical advice on how to design and implement them, Benedict and McMahon's book is a valuable resource for anyone who wants to understand innovative approaches to conservation-minded land use. From the individual parcel to the multi-state region, Green Infrastructure helps us look at the landscape in relation to the many uses it could serve, for nature and people, and determine which uses achieve the most benefits for both."--Jacket
Why green infrastructure? -- The green infrastructure approach : principles from past to present -- The benefits of a green infrastructure approach -- Where do we begin? -- The basics of network design -- The implementation quilt : matching available resources to network needs -- Management and stewardship -- Building support for green infrastructure -- Making it happen.
"The Conservation Fund."
Includes bibliographical references (pages 287-288) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Land use, Urban; Cities and towns -- Growth; Natural areas; Cultural property -- Protection; Utilisation urbaine du sol; Villes -- Croissance; Réserves naturelles; Patrimoine culturel -- Protection; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; Cities and towns -- Growth; Cultural property -- Protection; Land use, Urban; Natural areas; Electronic books; Electronic books